Function and therapeutic prospects of next-generation probiotic Akkermansia muciniphila in infectious diseases - Li, Lifeng; Li, Mingchao; Chen, Yihua; Yu, Zengyuan; Cheng, Ping; Yu, Zhidan; Cheng, Weyland; Zhang, Wancun; Wang, Zhaobao; Gao, Xueyan; Sun, Huiqing; Wang, Xiaolei (Frontiers in Microbiology, 2024)
Akkermansia muciniphila (A. muciniphila) is ana oval-shaped gram-negative bacterium that is a resident of colonizes the human gut, making up 3-5% of the human microbiome. A. muciniphila is a promising candidate of the next next-generation of probiotics with clinical application prospects. Emerging studies have reported various beneficial effects of A. muciniphila including anti-cancer, delaying aging, reducing inflammation, improving immune function, regulating nervous system function, whereas knowledge on its roles and mechanism in infectious disease is currently unclear.In this review, we provide an overview of summarized the basic characteristics, genome and phenotype diversity, pathophysiological impact the influence of A. muciniphila and its derived components on infectious diseases, such as sepsis, virus infection, enteric infection, periodontitis and foodborne pathogen induced infections.We also provided updates on mechanisms how A. muciniphila enhances protects intestinal barrier integrity and regulates modulate host immune response. In summary, we believe that A. muciniphila is a promising therapeutic probiotic that may be a potential target applied for the treatment of a variety of infectious diseases.